Analisis Efektivitas Penerapan Strategi Pemasaran Dalam Meningkatkan Hunian Kamar Pada Sheraton Hotel and Restaurant Lombokdi Masa Pandemi Covid 19 - Prana, Satrio Adi; Nurhidayati, Nurhidayati; Haulia, Nurul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this study was to determine whether the marketing strategy applied to Sheraton Hotel and Restaurant Lombokwas effective in increasing room occupancy. The method used in this research is descriptive method, and the population is the guests (customers) who stay at Sheraton Hotel and Restaurant Lombok. Determination of the sample in the study using the Yamane formula with a precision level of 10% with a confidence level of 90%, so that the results obtained amounted to 83 people. The sampling technique used is purposive sampling and accidental sampling, using library data collection techniques and field studies which include observation, interviews and questionnaires. And to analyze the data obtained is a single table data analysis technique. The results of this study indicate that the marketing strategy applied to Sheraton Hotel and Restaurant Lombok has been effective in increasing room occupancy, as evidenced by the number of full rooms and the number of guests staying and the condition of the hotel, rooms and facilities available in accordance with the wishes and needs of guests (customers). . And it was also found that visitors who stay feel like, happy and satisfied with the services of this hotel.